Comparison of glycosylated fibronectin versus soluble fms-like tyrosine kinase/placental growth factor ratio testing for the assessment of pre-eclampsia: protocol for a multicentre diagnostic test accuracy study - Marcus Green; Chao Wang; Sarah Fisher; Amarnath Bhide; Ramesh Ganapathy; Basky Thilaganathan; Nouran Elbarbary (BMJ Open)
Introduction Pre-eclampsia is a condition associated with significant maternal and neonatal morbidity and mortality. The prediction of pre-eclampsia in high-risk populations using angiogenic markers, such as serum placental growth factor (PlGF) assessment, has been shown to improve maternal outcomes and is recommended by the National Institute for Health and Care Excellence (NICE). However, such tests are not yet available at the point of care (POC). Glycosylated fibronectin (GlyFn) level for the prediction of pre-eclampsia development is available as a POC test (Lumella) and has the potential to aid rapid clinical decision making. This study aimed to test the hypothesis that the sensitivity of the GlyFn test is not inferior to that of the current gold standard of soluble fms-like tyrosine kinase (sFlt)/PlGF-based laboratory testing for pre-eclampsia.Methods and analysis This is a multicentre prospective study. Women at risk for pre-eclampsia based on predefined clinical and/or obstetric risk factors will be invited to participate in the study. The recruitment target is 400 participants. Consenting participants will have paired samples for sFlt/PlGF together with POC GlyFn testing. Two follow-up visits are planned at 2 and 4 weeks after the initial recruitment where repeat testing with both tests will be performed. The clinical team will be blinded to the results of the GlyFn test but not that of the sFlt/PlGF test. Clinical care will be based on established protocols incorporating maternal/fetal evaluation and the results of sFlt/PlGF levels. Maternal and neonatal outcome data will be collected to compare the sensitivity and specificity of the tests, with the primary outcome being delivery for pre-eclampsia within 4 weeks.Ethics and dissemination Ethical approval has been obtained from the Health Research Authority and Health and Care Research Wales Ethics Committee. The results of this study will be published in peer-reviewed journals and presented at scientific conferences.Trial registration number ISRCTN13430018